Maternal L-Carnitine Supplementation Improves Brain Health in Offspring from Cigarette Smoke Exposed Mothers - Chan, Yik Lung; Saad, Sonia; Al-Odat, Ibrahim; Oliver, Brian G.; Pollock, Carol; Jones, Nicole M.; Chen, Hui (Frontiers in Molecular Neuroscience, 2017)
Maternal cigarette smoke exposure (SE) causes detrimental changes associated with the development of chronic neurological diseases in the offspring as a result of oxidative mitochondrial damage. Maternal L-Carnitine administration has been shown to reduce renal oxidative stress in SE offspring, but its effect in the brain is unknown. Here, we investigated the effects of maternal L-Carnitine supplementation on brain markers of oxidative stress, autophagy, mitophagy and mitochondrial energy producing oxidative phosphorylation complexes (OXPHOS) in SE offspring. Female Balb/c mice (8 weeks) were exposed to cigarette smoke prior to mating, during gestation and lactation with or without L-Carnitine supplementation (1.5mM in drinking water). In 1 day old male SE offspring, brain mitochondrial damage was suggested by increased mitochondrial fusion and reduced autophagosome markers; whereas at 13 weeks, enhanced brain cell damage was suggested by reduced fission and autophagosome markers, as well as increased apoptosis and DNA fragmentation markers, which were partially reversed by maternal L-Carnitine supplementation. In female SE offspring, enhanced mitochondrial regeneration was suggested by decreased fission and increased fusion markers at day 1. At 13 weeks, there was an increase in brain energy demand, oxidative stress and mitochondrial turnover, reflected by the protein changes of OXPHOS complex, fission and autophagosome markers, as well as the endogenous antioxidant, which were also partially normalised by maternal L-Carnitine supplementation. However, markers of apoptosis and DNA fragmentation were not significantly changed. Thus L-Carnitine supplementation may benefit the brain health of the offspring from smoking mothers.